KINERJA RUMAH SAKIT TIPE C DENGAN PENDEKATAN BALANCED SCORECARD - Yenni Fayanni (Behavioral Accounting Journal, 2018)
This study aims to determine and analyze and evaluate the performance measurement system using Balanced Scorecard approach on Petrokimia Gresik Hospital. This research uses a qualitative approach with several informants and documents which in fact Petrokimia Gresik Hospital has not fully implemented the performance measurement with balanced scorecard approach so that there is unique phenomenon that interesting to be investigated deeper.The results showed that the performance measurement system at Petrokimia Gresik hospital was conducted by reviewing the strategic objectives of the size, target and the initiatives used to achieve the strategic objectives. The implication of the research result shows that the performance measurement system applied in Petrokimia Gresik Hospital is not maximal yet, so it needs additional indicators from the perspective of customer perspective, growth perspective and learning to sharpen the performance measurement system and can implement the performance measurement by using balanced scorecard.